Improving thermal model for oil temperature estimation in power distribution transformers. (5th June 2017) - Najar, Sami; Tissier, Jean-Francois; Cauet, Sebastien; Etien, Erik
Highlights: A method of oil temperature estimation of ONAN distribution transformer is proposed. A identification process using Levenberg-Marquardt algorithm improves IEC 60076-7 standard. The oil temperature soft sensor can be implemented in a smart meter. Experimental results with three distribution transformers show the effectiveness of the approach. Abstract: This paper presents a method estimating the oil temperature for ONAN distribution transformers. A Levenberg-Marquardt algorithm improving the reliability of standard IEC 60076-7 thermal model is developed. An oil temperature model, based on standard parameters is compared with that given by the proposed identification procedure. The improvement of temperature estimation is highlighted and validated on three distribution transformers from 160 kVA to 800 kVA.